1965
DOI: 10.1302/0301-620x.47b3.560
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Anastomoses of Arteries Supplying the Head and Neck of the Femur

Abstract: 1. At necropsy the arterial distribution within the head and neck of the femur was investigated by arteriographic injection in fifty-seven uninjured hips of mostly elderly subjects. 2. Before injection all vessels to the head except for one or more particular groups were divided. 3. The superior retinacular arteries were found to be the most important arterial supply to the head. Through the widely distributed branches of their lateral epiphysial vessels (superior capital) they supplied the superior, medial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1
12

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(112 citation statements)
references
References 4 publications
3
96
1
12
Order By: Relevance
“…However, with regard to the distinctive characteristics of each insertion, the present investigation was unique because it quantified the number of vessels in the calcified fibrocartilage and cortical bone of the proximal femur. Typically, investigations of the blood supply to the proximal femur have made qualitative macroscopic observations and have not examined the microvascularity or vessel density (Howe and Schwartz, 1950;Judet et al, 1955;Crock, 1965;Sevitt and Thompson, 1965). The present investigation observed that there were no regional differences in the vascular density of the cortical bone beneath the insertions of the dorsal neck and the greater and lesser trochanters.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…However, with regard to the distinctive characteristics of each insertion, the present investigation was unique because it quantified the number of vessels in the calcified fibrocartilage and cortical bone of the proximal femur. Typically, investigations of the blood supply to the proximal femur have made qualitative macroscopic observations and have not examined the microvascularity or vessel density (Howe and Schwartz, 1950;Judet et al, 1955;Crock, 1965;Sevitt and Thompson, 1965). The present investigation observed that there were no regional differences in the vascular density of the cortical bone beneath the insertions of the dorsal neck and the greater and lesser trochanters.…”
Section: Discussioncontrasting
confidence: 45%
“…Despite the importance of vascularity, there has been very little research into the microvascular supply to the proximal femur or to the tendon and ligament insertions in this region. A majority of the studies that have examined vascularity have focused on identifying the major blood vessels supplying this important structural region (Howe and Schwartz, 1950;Judet et al, 1955;Crock, 1965;Sevitt and Thompson, 1965;Gautier et al, 2000), and not on the microvasculature. In addition, it has recently been shown that up to 60% of the cortical shell of the human proximal femur is composed of a hypermineralized calcified fibrocartilage been shown at other anatomical sites to be an avascular tissue (Petersen and Tillmann, 1999;Benjamin et al, 2000).…”
mentioning
confidence: 99%
“…The flap so created contains the deep branch of the medial femoral circumflex artery, the anastomoses with the inferior gluteal artery, and its retinacular end branches; it clearly is longer than with the retinacular tunneling produced with the classic Dunn procedure [14] and therefore allows better compensation of adverse stretching during manipulation. After developing the posterolateral flap portion, we created an anteromedial flap containing a constant branch of the medial femoral circumflex artery, running in the synovial surface of Weitbrecht's ligament and giving blood supply to the inferomedial portion of the epiphysis [43], again with strictly subperiosteal dissection. Both flaps were connected posteriorly and allowed circumferential access to the osseous neck.…”
Section: Methodsmentioning
confidence: 99%
“…Atsumi et al & Sevitt et al [17,18]. found that there are no radiological necrosist onset, missing the vessels in the capsule of the upper femoral neck completely.…”
Section: Discussionmentioning
confidence: 98%
“…They found that there is no radiological necrosist onset, missing the vessels in the capsule of the upper femoral neck completely [17]. But these are just responsible for the vascularization of the greater part of the femoral head and the nerve fiber density of the femoral head as already Sevitt et al [18] has described.…”
Section: Introductionmentioning
confidence: 89%